1999
DOI: 10.1046/j.1365-2613.1999.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide protects the ultrastructure of pancreatic acinar cells in the course of caerulein‐induced acute pancreatitis

Abstract: Nitric oxide (NO) as a unique biological mediator that has been implicated in many physiological and pathophysiological processes may have a significant influence on the course of acute pancreatitis and the recovery process. The aim of the study was to evaluate the effect of a NO synthase inhibitor or a substrate for NO endogenous production on the ultrastructural features of the acinar cells in the course of caerulein-induced acute pancreatitis. Acute pancreatitis was induced in the rats by a supramaximal dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Caerulein is an agent used for hyperstimulation of AP in experimental models [4][5][6][7]. Caerulein is a decapeptide and the analog of cholecystokinin, which has a similar effect to cholecystokinin.…”
Section: Introductionmentioning
confidence: 99%
“…Caerulein is an agent used for hyperstimulation of AP in experimental models [4][5][6][7]. Caerulein is a decapeptide and the analog of cholecystokinin, which has a similar effect to cholecystokinin.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous model of caerulein-induced acute pancreatitis, Werner et al [14] found that L-NAME treatment increased the severity of inflammation, while decreasing pancreatic tissue oxygenation. In addition both Konturek et al [11] and Andrzejewska and Jurkowska [13] found that L-NNA significantly potentiated inflammatory changes in pancreas induced by caerulein injection.…”
Section: Discussionmentioning
confidence: 96%
“…Rats that received L-arginine alone, or in combination with the NO synthase inhibitor N(G)-nitro-L-arginine (L-NNA), experienced augmented cell proliferation after acute pancreatitis induction followed by earlier recovery compared with those with untreated acute pancreatitis or that only received L-NNA [12]. In another study, Andrzejewska and Jurkowska [13] demonstrated that while L-arginine treatment reverses some of the deleterious effects of L-NNA, it does not affect acinar cell ultrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes and macrophages can initiate or aggravate cell damage through different mechanisms, including ROS, cytokines and a large quantity of nitric oxide produced by the inducible NOS [26,29,30]. NO has been found to be beneficial in protection of the ultrastructure of pancreatic acinar cell in AP [31]. We have determined beneficial effects of L-arginine on histopathological pancreatic damage and on increases in serum amylase and lipase levels during acute experimental pancreatitis (unpublished data).…”
Section: Groupsmentioning
confidence: 94%